A-49 To Nap or Not to Nap? The Influence of Napping on Recovery Outcomes Following Concussion. (18th June 2020) - Zynda, A J; Petit, K M; Anderson, M; Tomczyk, C P; Covassin, T
Abstract: Objective: To determine the influence of nap frequency on daily symptom severity and recovery time following concussion in college students. Method: A prospective study of college students within 72 hours of a diagnosed concussion was performed. Participants reported nap occurrence (yes/no) and daily concussion symptoms using the Post-Concussion Symptom Scale (PCSS) for six days. Participants were categorized into frequent (>2 naps) and infrequent (<3 naps) nap groups. Recovery time was defined as total days from injury to unrestricted medical clearance. A mixed between-within ANOVA evaluated changes in daily symptom severity between nap groups, while Spearman's Rank Correlation assessed the relationship between the number of days napping and recovery time. Results: Thirty-four participants (23 female, 11 male; age = 19.91 ± 1.38 years) were included, with 22 in the infrequent nap group and 12 in the frequent nap group. Average recovery time for the infrequent nap group was 13.85 days compared to 18.8 days in the frequent nap group. There was no significant group x time interaction for daily symptom severity (Wilks' λ = 0.85, F(5, 24) = 0.85, p = 0.53, η 2 = 0.15). There was a significant main effect for time, with daily symptom severity improving following concussion (Wilks' λ = 0.31, F(5, 24) = 10.66, p < 0.001, η 2 = 0.69), but there was no significant group effect (F(1, 28) = 0.79, p = 0.38, η 2 = 0.03). Overall, the more naps taken, the longer the recovery time (Rs = 0.46, p = 0.01). Conclusions: Findings from the present study suggest that frequent napping does not affect symptom severity following concussion. Further research is needed to elucidate the association between the number of naps and recovery time.